Generalized Surgical Emphysema in Open Pelvic Fracture: a case report - Paudel, Byapak; Pandey, Chakra Raj (Nepal Orthopaedic Association Journal, 2013)
Open fractures of the pelvis are rare and potentially lethal injuries with mortality rate ranging from 30 % to 50 %. Subcutaneous surgical emphysema over the pelvis in open pelvis fracture has been reported in literature but generalized surgical emphysema in open pelvis fracture has not been reported previously. We present and discuss here a case of 24 years old man who had sustained Road traffic accident resulting in multiple fractures and developed generalized surgical emphysema. DOI: http://dx.doi.org/10.3126/noaj.v3i1.9323 Nepal Orthopedic Association Journal 2013 Vol.3(1): 28-30